From Ridge 2 Reef: An interdisciplinary model for training the next generation of environmental problem solvers. - Raechel J Hill; Matea A Djokic; Andrea Anderson; Kristin Barbour; Amanda M Coleman; Alexis D Guerra; Courtney Hunt; Amber Jolly; Jennifer J Long; Kyle T Manley; Jonathan L Montoya; Carl A Norlen; et al. (PLoS ONE)
Regional and global environmental challenges have become increasingly complex and require broader solutions than a single discipline can provide. Although there is a growing need for interdisciplinary research, many graduate education programs still train students within the confines of a particular discipline or specialty. The Ridge 2 Reef research traineeship program at the University of California, Irvine, aimed to provide transferable and interdisciplinary skill training to prepare graduate students from different disciplines to address current and future environmental challenges. The program achieved its goals through a 'culture of improvement' that ensured trainee needs shaped program management and curriculum. Due to trainee feedback and leaders dedicated to program improvement, there was a complete course overhaul during the first two years of the program, resulting in a final curriculum structure that was more effective and aligned with revised program goals. Program evaluations suggest that the flexibility of the program, diversity of training, overhauled courses offered, and partnership-focused opportunities contributed to more confident graduate students who were more broadly trained and better prepared in their chosen environmental career paths. Based on evaluation surveys, graduate students reported significant gains in scientific, technical, and career knowledge as well as transferrable skills in communication, data analysis, leadership, mentoring, and interdisciplinary collaboration. The structure and evolution of the Ridge 2 Reef traineeship can provide a framework for other graduate education programs to better incorporate interdisciplinary training and student feedback, ultimately improving programs and preparing scientists for the 21st century workforce.